A CCSEM study on the transformation of included and excluded minerals during coal devolatilization and char combustion. (15th May 2016) - Wen, Chang; Gao, Xiangpeng; Xu, Minghou
Highlights: Quartz is generally stable during coal devolatilization but transferable during char combustion. Excluded calcite and siderite interact with aluminosilicates during coal devolatilization. Interactions between Fe/Ca-rich minerals and aluminosilicates are confirmed. Such interactions occur during both coal devolatilization and char combustion. Abstract: This study reports the transformation pathways of both included and excluded minerals during coal devolatilization and char combustion. Three Chinese coals of various ranks, namely YQ anthracite, DT bituminous coal and CF lignite, were size narrowed to 45−100 μm, devolatilized in nitrogen and combusted in air at 1300 °C, using a laboratory-scale drop tube furnace, to prepare chars and ashes. The mineral properties of the coals as well as their derived chars and ashes were analyzed using a computer-controlled scanning electron microscopy (CCSEM). The results demonstrate that, during coal devolatilization, whereas quartz and kaolinite are generally stable for all the three coals, included and excluded Fe-rich minerals (i.e., pyrite and siderite) as well as excluded Ca-rich minerals (i.e., calcite and ankerite) are decomposed and some of the intermediate products are incorporated with aluminosilicates. During char combustion, quartz participates in combustion reactions and forms aluminosilicates. Whereas the mullite-like phase in the YQ and DT chars changes little, that in the CF char absorbs Fe/Ca-rich fine particles and is incorporated into Fe–Ca-aluminosilicate. Most of the Ca/Fe-rich intermediate products react with aluminosilicates to form Fe-, Ca-, and Fe–Ca-aluminosilicates. The interactions between Fe/Ca-rich minerals and aluminosilicates are also observed. Calcium in Ca-rich minerals and iron in Fe-rich minerals of the YQ anthracite and the CF lignite interact with aluminosilicates during both coal devolatilization and char combustion processes. However, for the DT bituminous coal, such interactions between Ca-rich minerals and aluminosilicates only take place during devolatilization. The interactions between excluded Fe/Ca-rich minerals and included aluminosilicates during coal devolatilization are also observed.